PROFIL RESPIRATORY DISTRESS PADA BAYI BARU LAHIR DI NICU RSIA SITI HAWA PADANG TAHUN 2021 - Eldrian, Febiane; Liana, Nana; Aditia Permana, Yudhi; Lismawati; Helmizar, Roland (Nusantara Hasana Journal, 2024)
Respiratory distress (RD) poses a significant issue that can lead to fatal consequences such as respiratory failure, brain damage, and an increase in morbidity and mortality among newborns. The diagnosis of RD is based on the identification of one or more signs of increased respiratory activity, including tachypnea, nasal flaring, retractions in the intercostal area, and grunting. Objective: The purpose of this research is to provide an overview of the occurrence of RD among neonatus who were hospitalized in the Neonatal Intensive Care Unit (NICU) at RSIA Siti Hawa Padang in the year 2021. Methods: This study is an analytic descriptive research. The accessible population in this study consists of newborns who were treated at the NICU of RSIA Siti Hawa Padang during the year 2021. Results: From the study findings, it was observed that 94 newborns (approximately 5.2%) experienced RD. Among them, males were more predominant, accounting for 54 infants (57%). The majority of infants had a gestational age categorized as full-term, totaling 56 infants (59.6%). Furthermore, the birth weight for the majority of newborns was within the normal range, with 65 infants (69.1%) falling into this category. Conclusion: In conclusion, the majority of newborns at NICU RSIA Siti Hawa Padang in 2021 did not experience RD. Among those affected by RD, males were predominant, and most had a gestational age categorized as full-term, indicating a low risk of prematurity. The average birth weight also tended to be within the normal range for newborns born and cared for in NICU RSIA Siti Hawa Padang in 2021.